2020
DOI: 10.1155/2020/6814263
|View full text |Cite
|
Sign up to set email alerts
|

Two Improved Methods of Generating Adversarial Examples against Faster R-CNNs for Tram Environment Perception Systems

Abstract: Trams have increasingly deployed object detectors to perceive running conditions, and deep learning networks have been widely adopted by those detectors. Growing neural networks have incurred severe attacks such as adversarial example attacks, imposing threats to tram safety. Only if adversarial attacks are studied thoroughly, researchers can come up with better defence methods against them. However, most existing methods of generating adversarial examples have been devoted to classification, and none of them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Wang et al 10 suggested an adversarial attack method to fool faster R-CNN object detection networks. Huang et al 11 developed an improved classifier attack algorithm that can be applied to object detection. Wang et al 31 suggested an effective adversarial attack strategy for several kinds of object identification models.…”
Section: Adversarial Attacksmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al 10 suggested an adversarial attack method to fool faster R-CNN object detection networks. Huang et al 11 developed an improved classifier attack algorithm that can be applied to object detection. Wang et al 31 suggested an effective adversarial attack strategy for several kinds of object identification models.…”
Section: Adversarial Attacksmentioning
confidence: 99%
“…suggested an adversarial attack method to fool faster R-CNN object detection networks. Huang et al 11 . developed an improved classifier attack algorithm that can be applied to object detection.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation